Place of Religious Groups in the Democratic States - Samaneh Rahmatifar (حقوق بشر, 2022)
The purpose of this paper is to study the permission of the religious political parties in democratic governments. The research method is descriptive-analytical. Elements of democracy will be listed descriptively. A dialectical approach will apply to the response arguments of pro-religious parties, and the components of democracy will compare with the internal relations of such parties by comparative study. Although defenders of religious political parties mainly rely on political reasons, the findings show that legal reasoning is debatable to their arguments. The elements of democracy include public participation and control, equality, freedom, decision-making based on a numerical majority, pluralism, observing public interest, separation of powers, and the rule of law. These are incompatible with the nature of internal relationships in religious political parties. In addition to legal reasoning, the constitutional documents of some religious parties also support the hypothesis. The way of respecting the freedom of association as a principle established simultaneously by the international human rights law, and democracy, is the prohibition of religious groups as a political party without exception but instead recognition of their activity in the form of non-political civil institutions.